QUATERNARY GLACIATION IN THE HIGH MOUNTAINS OF CENTRAL AND NORTH-EAST ASIA - Sheinkman V.S. (My University, 2004)
Quaternary glaciation in the High Mountains of Central and North-east Asia is characterised by the interaction of glaciers and permafrost. The combined activities of these geological agents characterise the cryo-glacial systems (CGS) that shape the valleys of Central and North-east Asia. It requires an individual approach to each of the landforms and sediment bodies to determine if they can be interpreted as the relics of ancient glaciations. Most types of the CGS may be observed today along the mountainous belt surrounding Siberia from the south and east. They represent the key to the reconstruction of Quaternary environments because the range of climatic differences along this belt today is comparable to the range of climatic changes between Pleistocene glacial and interglacial conditions. During the Pleistocene cold stages, the continental climate promoted the spreading of permafrost under arid conditions (‘cryo-aridisation’). Since the ridges in the belt are comparable in height and in their cold continental environments, the extent of Quaternary glaciation was controlled by temperature. Under cryo-arid conditions, glaciers did not coalesce to form ice sheets. They developed only within the high mountains as valley glaciers. Consequently, glacial activity was inseparably linked with cryogenic ice in the proglacial and periglacial zone where icings were the most active agents. The latter occupied great areas and were comparable with the glaciers both in ice volume and in volume of geological work.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная